Role of Cu in the enhancement of NH3 sensing performance of spray pyrolyzed WO3 nanostructures. (October 2021) - Anusha,; Antony, Albin; Ani, Aninamol; Poornesh, P.; Kulkarni, Suresh D.
Abstract: Cu doped WO3 (Cu: WO3 ) films synthesized by chemical spray pyrolysis were explored for Ammonia (NH3 ) gas sensing. Obtained films were examined by X-ray diffraction technique (XRD), Scanning Electron Microscopy (SEM), UV–Visible spectroscopy (UV), Photoluminescence (PL), Raman and X-ray Photoelectron spectroscopy (XPS). XRD and Raman studies reveals the existence of monoclinic-I (γ-WO3 ) phase. Lower angle shift of (200) peak was noted in XRD for 3% Cu: WO3 primarily due to tensile strain developed in the WO3 lattice caused by Cu incorporation. SEM morphographs exhibited well defined grains on amalgamation of Cu in WO3 matrix. Photoluminescence studies showed enhancement in the oxygen vacancies upon Cu doping which plays crucial role in improving the sensor response. Gas sensing measurements of the films were performed at an operating temperature of 250 °C towards 1, 3 and 5 ppm concentration of NH3 gas. Incorporation of Cu into WO3 enhanced sensor response and shortened response time comapred to pristine WO3 films. 3% Cu doped WO3 showed good sensor response of 1.58 for 5 ppm concentration of NH3 .